A novel Cytochrome P450 26A1 expressing NK cell subset at the mouse maternal‐foetal interface. Issue 3 (12th January 2021) - Wei, Dan‐Ping; Li, Dan‐Dan; Gu, Ai‐Qin; Ji, Wen‐Heng; Yang, Ying; Peng, Jing‐Pian
Abstract: Cyp26a1 had important roles in mouse embryo implantation and was highly expressed in some of NK cells at the human maternal‐foetal interface in early pregnancy. However, the regulatory effect of Cyp26a1 on NK cells remains poorly understood. Through qPCR and flow cytometric assays, we found that Cyp26a1 was expressed by mouse uterine NK cells but not spleen NK cells during the peri‐implantation period and there was a group of NK cells that highly expressed Cyp26a1, that is Cyp26a1 + NK cell subset. single cell‐population transcriptome sequencing on Cyp26a1 + NK and Cyp26a1 − NK cell subsets was performed. We found that there were 3957 differentially expressed genes in the Cyp26a1 + NK cell subset with a cut‐off of fold change ≥2 and FDR < 0.01, 2509 genes were up‐regulated and 1448 genes were down‐regulated in Cyp26a1 + NK cell subset. Moreover, cytokine‐cytokine receptor interaction signalling pathway and natural killer cell–mediated cytotoxicity signalling pathway were enriched according to KEGG pathway enrichment analysis. We further found that the expression of Gzma and Klrg1 was significantly increased and Fcgr4 was significantly decreased when inhibiting Cyp26a1. Our experimental results show that there is a novel NK cell subset of Cyp26a1 + NK cells in mouse uterus and Cyp26a1 can regulate the gene expression of Gzma, Klrg1 and Fcgr4 in the Cyp26a1 + NK cells.